Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7150/thno.23369
|View full text |Cite
|
Sign up to set email alerts
|

2D Superparamagnetic Tantalum Carbide Composite MXenes for Efficient Breast-Cancer Theranostics

Abstract: Background: The emergence of two-dimensional MXenes has spurred their versatile applications in broad fields, but the exploring of novel MXene-based family members and their potential applications in theranostic nanomedicine (concurrent diagnostic imaging and therapy) have been rarely explored. In this work, we report the construction of a novel superparamagnetic MXene-based theranostic nanoplatform for efficient breast-cancer theranostics, which was based on intriguing tantalum carbide (Ta4C3) MXene and its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(151 citation statements)
references
References 50 publications
(42 reference statements)
5
142
0
2
Order By: Relevance
“…Although research into MXenes has expanded very fast and captured much attention in the areas of energy storage, sensing, and catalysis, the biomedical applications of MXenes are still in their infancy. Due to their remarkable photothermal performance, multimodal imaging ability, and excellent biocompatibility, MXenes have already been used for cancer theranostics . However, only a few reports to date have documented the antibacterial activity of MXenes, which implies a need for further investigation of this aspect.…”
Section: Antibacterial Activity Of 2d Materials Beyond Gmsmentioning
confidence: 99%
“…Although research into MXenes has expanded very fast and captured much attention in the areas of energy storage, sensing, and catalysis, the biomedical applications of MXenes are still in their infancy. Due to their remarkable photothermal performance, multimodal imaging ability, and excellent biocompatibility, MXenes have already been used for cancer theranostics . However, only a few reports to date have documented the antibacterial activity of MXenes, which implies a need for further investigation of this aspect.…”
Section: Antibacterial Activity Of 2d Materials Beyond Gmsmentioning
confidence: 99%
“…In particular, the high PTCE of these magnetic MXenes ensures the efficient photothermal eradication of cancer cells and ablation of tumor tissues, as demonstrated both in vitro and in vivo. Ta 4 C 3 –IONP nanocomposite MXenes have also been demonstrated to be efficient breast‐cancer theranostics through bimodal CT/MR imaging‐guided PTT . Recently, our group also constructed multifunctional 2D Ti 3 C 2 @Au nanocomposites for bimodal‐imaging‐guided cancer therapy in the NIR‐II range .…”
Section: Mxene Nanosheetsmentioning
confidence: 98%
“…B) 2D superparamagnetic tantalum carbide (Ta 4 C 3 –IONP–SPs) nanocomposites for dual‐modal contrast‐enhanced MRI/CT‐imaging‐guided PTT. Reproduced with permission . Copyright 2018, Ivyspring International Publisher.…”
Section: Mxene Nanosheetsmentioning
confidence: 99%
“…LDHs consist of hydroxide host layers and interlayer anions, with the general formula of [M 2+ 1− x M 3+ x (OH) 2 ](A n − ) x / n · m H 2 O (Gao & Yan, ; D. Liu, Lin, Tang, Deng, & Bi, ; Z. Liu, Lin, Zhao, et al, ; C. Liu, Qin, et al, ; W. Liu, Xu, et al, ; Shao et al, ; Tian et al, ; Q. Wang & O'Hare, ). Notably, LDHs nanosheets can be taken up by specific types of cancer cells via clathrin‐mediated endocytosis, thus leading to the resistance to endosomal effects with buffering properties (G. Choi et al, ).…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
“…For example, g‐C 3 N 4 nanosheets have been developed as drug delivery response to pH for effective cancer therapy (S. Liu et al, ). In another recent study, it has been reported that g‐C 3 N 4 nanosheets exhibit high drug loading capacity towards DOX (D. Liu, Lin, Tang, et al, ; Z. Liu, Lin, Zhao, et al, ; C. Liu, Qin, et al, ; W. Liu, Xu, et al, ). Interestingly, because of the excellent fluorescence imaging ability of g‐C 3 N 4 nanosheets, the drug delivery process can be directly visualized for potential diagnostic purpose (Figure a).…”
Section: Other 2d Nanomaterials For Drug Deliverymentioning
confidence: 99%